2018
DOI: 10.21276/aabs.2336
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nutritional Status and Pressure Ulcers Healing in Spinal Cord Injury SubjectsA Non-randomized, Non-controlled Quasi Experimental Study

Abstract: Objective: This study was done to determine the cause effect relationship between pressure ulcers (PUs) and metabolic alterations in individual having PUs with Spinal Cord Injury (SCI) Methods: 123 SCI subjects with PUs were enrolled in the study. PUs were measured for surface area, exudate, depth and formation of granulation tissue using the pressure ulcers scale for healing tool. The nutritional status of subjects was assessed by measuring serum haemoglobin, albumin and transferrin levels at baseline (week 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Patients with high incomes could afford to buy specialised assistive devices such as wheelchair cushions to aid in preventing SHCs. Those with low income could not even manage to get a healthy diet compromising their nutritional status, thus increasing the risk of the development of SHCs and delaying wound healing for those with an existing pressure sore (Bhagat et al 2018 ). There is also a link between lack of finances and mental problems (Zürcher, Tough & Fekete 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with high incomes could afford to buy specialised assistive devices such as wheelchair cushions to aid in preventing SHCs. Those with low income could not even manage to get a healthy diet compromising their nutritional status, thus increasing the risk of the development of SHCs and delaying wound healing for those with an existing pressure sore (Bhagat et al 2018 ). There is also a link between lack of finances and mental problems (Zürcher, Tough & Fekete 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence linking the reoccurrence of UTI to malfunctioning of an innate immune activation gene (Godaly, Ambite & Svanborg 2015 ), meaning that even if an individual practices good bladder management UTI will still occur. Nutritional deficiencies have also been linked to delayed pressure sore healing (Bhagat et al 2018 ). Thus, intrinsic factors influencing health, health outcomes and prevention of diseases are many, ranging from genetic predisposition to psychological, mental and physical status.…”
Section: Introductionmentioning
confidence: 99%
“…Khalil [74] explained properly design dietary interventions are required that suit the adaptations following SCI. Bhagat [75] suggested that routine nutritional screening should result in early identification of risk of developing pressure ulcers.…”
Section: Miscalleneous Nutrition Supplementation Datamentioning
confidence: 99%